Stomach contents of diving and dabbling ducks during fall migration in the St. Lawrence River, Quebec, Canada - Guillemette, Magella; Bolduc, François; Desgranges, Jean-Luc (Wildfowl, 2025)
Stomach contents of ten duck species feeding on benthos were analyzed in the context of new prey species invading the St. Lawrence river, eastern Canada. One hundred and twenty-three stomachs (123) belonging to eight species of diving ducks and two species of dabbling ducks were analyzed. The amount of food found in the stomachs was low and seems to be related to the fact that the great majority of ducks were collected while flying. A bias in food composition was associated with duck species characterized by residual contents in their gizzard, which were discarded from our analysis. In general, the diet of diving ducks was mainly animal while plant material dominated the diet of dabbling ducks. The most important group of animal prey was the gastropods, two species from which dominated the diet of diving ducks, namely Bethany tentaculata and Viviparus sp. These two prey species are European in origin and were apparently introduced in the St. Lawrence several decades ago. This leads us to suggest that the recent introduction of the Zebra Mussel Dreissena polymorpha in the St. Lawrence could significantly alter the diet of diving ducks in the future. Incidentally, one specimen of Surf Scoter Melanitta perspicillata had its gizzard filled with this species.